Theta-burst versus 20 Hz repetitive transcranial magnetic stimulation in neuropathic pain: A head-to-head comparison. Issue 10 (October 2021) - André-Obadia, N.; Magnin, M.; Garcia-Larrea, L.
Highlights: 20 Hz-rTMS induced more pronounced pain-relief than iTBS. Scores of chronic fatigue decreased to a greater extent after 20 Hz-rTMS than iTBS. Matching of rTMS frequency and intrinsic cortical oscillations may potentiate efficacy. Abstract: Objective: High-frequency repetitive transcranial magnetic stimulation (rTMS) has been shown to reduce neuropathic pain, but intermittent "theta-burst" stimulation (iTBS) could be a better alternative because of shorter duration and greater ability to induce cortical plasticity. Here we compared head-to-head the pain-relieving efficacy of the two modalities when applied daily for 5 days to patients with neuropathic pain. Methods: Forty-six patients received 20 Hz-rTMS and/or iTBS protocols and 39 of them underwent the full two procedures in a random cross-over design. They rated pain intensity, sleep quality, fatigue and general health status daily during 5 consecutive weeks. Results: Pain relief during the month following stimulation was superior after 20 Hz-rTMS relative to iTBS (F(1, 38) = 4.645; p = 0.037). Correlation between respective levels of maximal relief showed a significant deviation toward the 20 Hz-rTMS effect. A greater proportion of individuals responded to 20 Hz-rTMS (52% vs 32%, 95 %CI[0.095–3.27]; p = 0.06), and reports of fatigue significantly improved after 20 Hz-rTMS relative to iTBS (p = 0.01). General health and sleep quality scores did not differentiate both techniques. Conclusions: High-frequency rTMS appeared superior to iTBS for neuropathic pain relief. Significance: Adequate matching between the oscillatory activity of motor cortex and that of rTMS may increase synaptic efficacy, thus enhancing functional connectivity of motor cortex with distant structures involved in pain regulation.